2021
DOI: 10.1097/hjh.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and renal prognosis of left ventricular diastolic dysfunction in non-dialysis chronic kidney disease patients with preserved systolic function

Abstract: Background: Left ventricular (LV) diastolic dysfunction is common in non-dialysis chronic kidney disease (ND-CKD) patients; however, the prevalence estimated according to the new diagnostic criteria as well as the prognostic role of diastolic dysfunction on CKD progression remain unknown. Method:We longitudinally evaluated consecutive ND-CKD patients and preserved systolic function (LV ejection fraction > 50%). According to the recently updated guidelines, LV diastolic dysfunction was assessed by four echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Patients with CKD are at a higher risk of cognitive impairment, and older patients on dialysis have the highest absolute risk ( 4 ). Neuroimaging studies have shown that patients with CKD tend to have structural and functional changes, such as white matter hyperintensities, asymptomatic stroke, and brain atrophy ( 5 , 6 ). The white matter of the brain acts as a relay station for the central nervous system and is responsible for the exchange of information and communication between different gray matter areas ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CKD are at a higher risk of cognitive impairment, and older patients on dialysis have the highest absolute risk ( 4 ). Neuroimaging studies have shown that patients with CKD tend to have structural and functional changes, such as white matter hyperintensities, asymptomatic stroke, and brain atrophy ( 5 , 6 ). The white matter of the brain acts as a relay station for the central nervous system and is responsible for the exchange of information and communication between different gray matter areas ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of diastolic dysfunction has been recently suggested to be a useful tool for predicting the development of adverse renal outcomes, defined as a >50% decrease in estimated GFR from baseline, doubling of serum creatinine, dialysis initiation and/or kidney transplantation [ 97 ], although no adjustment for LV geometry and geometry-independent systolic function was considered (only ejection fraction was used as a measure of systolic function). However, this has also been demonstrated in patients with preserved systolic function (defined as an ejection fraction >50%), further demonstrating that diastolic heart dysfunction is a risk factor for CKD progression, also after adjusting for the presence of body surface area–based LV hypertrophy [ 98 ], but not for other factors that might influence disease progression for both the heart and kidney (Fig. 4 ).…”
Section: Introductionmentioning
confidence: 77%
“…The pathogenesis of LV diastolic dysfunction in CKD patients includes abnormal ventricular filling in diastole and a higher left ventricular filling pressure because of LVH, in addition to myocardial interstitial fibrosis [ 19 ]. As a consequence, this condition is commonly found in pre-dialysis CKD subjects, even with preserved systolic function [ 20 ], as well as in hemodialysis patients [ 21 ]. Importantly, the prevalence of diagnosed diastolic dysfunction differed significantly as it was dependent on the older (2009) or newer (2016) ASE/EACVI criteria used [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, this condition is commonly found in pre-dialysis CKD subjects, even with preserved systolic function [ 20 ], as well as in hemodialysis patients [ 21 ]. Importantly, the prevalence of diagnosed diastolic dysfunction differed significantly as it was dependent on the older (2009) or newer (2016) ASE/EACVI criteria used [ 20 , 22 ]. However, as volume overload and dyspnea symptoms, used in the cornerstone NYHA classification, are more commonly seen in CKD population, new, CKD-tailored criteria for heart failure diagnosis were proposed by the Acute Dialysis Quality Initiative (ADQI) a decade ago [ 23 ].…”
Section: Discussionmentioning
confidence: 99%